2005
DOI: 10.1210/en.2004-0466
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Cytokine Signaling-3 Provides a Novel Interface in the Cross-Talk between Angiotensin II and Insulin Signaling Systems

Abstract: Angiotensin II inhibits insulin-induced activation of phosphatidylinositol 3-kinase through a mechanism, at least in part, dependent on serine phosphorylation of the insulin receptor and insulin receptor substrates (IRS)-1/2. Recent evidence shows that suppressor of cytokine signaling-3 (SOCS-3) is induced by insulin and angiotensin II and participates in the negative control of further stimulation of each of these signaling systems independently. In the present study, we evaluated the interaction of angiotens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 47 publications
1
41
0
2
Order By: Relevance
“…Cross-talk between the RAS and the insulin signaling system has drawn great attention because hypertension and insulin resistance often coexist (Calegari et al 2005, Velloso et al 2006. It has been shown that Ang II infusion induces insulin resistance as well as a substantial reduction in glucose disposal in normal skeletal muscle (Rao 1994, Richey et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-talk between the RAS and the insulin signaling system has drawn great attention because hypertension and insulin resistance often coexist (Calegari et al 2005, Velloso et al 2006. It has been shown that Ang II infusion induces insulin resistance as well as a substantial reduction in glucose disposal in normal skeletal muscle (Rao 1994, Richey et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…The outstanding improvement in the molecular activation of this pathway, achieved with infliximab, may be the result of an alleviation of the functional activities of serine kinases, such as JNK and IkBK, which are targets of TNF-a and can affect insulin signaling by promoting the inhibitory serine phosphorylation of IR, IRS1, and IRS-2 (Paz et al 1997, Hirosumi et al 2002, Araujo et al 2005. The JAK2/STAT3 is a non-classical target of insulin signaling (Saad et al 1996) that participates in the crosstalk of the insulin signaling with several other pathways (Calegari et al 2005, including inflammatory pathways activated by cytokines. In addition, the JAK2/STAT3 pathway is a primary target for leptin signaling, a hormone known to exert anti-steatotic effects (Lee et al 2001) and to be modulated by a crosstalk with insulin (Carvalheira et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the tissue or cell line studied, insulin is able to induce the expression of SOCS-2 [69] and/or SOCS-3 [68,73] through the activation of STAT-5b. Once induced, SOCS-3 can bind to the Tyr 960 of the IR and hamper its capacity to induce the tyrosine phosphorylation of STAT5b, IRS-1 and IRS-2 [68,70,74].…”
Section: The Late Events Affected By the Insulin-ang II Cross-talkmentioning
confidence: 99%
“…When SOCS-3 is induced by Ang II in the heart and isolated cardiomyocytes, it interacts not only with the proteins of the Ang II signaling pathway but also with proteins that belong to the classical insulin signaling pathway [73] (Figure 2(c)). The time frames of these associations are closely related to the time frame required for Ang II to induce the expression of SOCS-3.…”
Section: The Late Events Affected By the Insulin-ang II Cross-talkmentioning
confidence: 99%
See 1 more Smart Citation